Rasch measurement and strategies of Science Teacher's Technological, Pedagogical, and Content Knowledge in Augmented Reality - Cyril, Nelson; Jamil, Nor Aisah; Mustapha, Zainun; Thoe, Ng Khar; Ling, Loh Su; Anggoro, Subuh (Universitas Muhammadiyah Purwokerto, 2023)
The use of Augmented Reality in the Teachers’ Technological, Pedagogical, and Content Knowledge (TPACK) framework is one of the systematic approaches to enriching students' experience in a science classroom. A study was conducted to explore teachers’ TPACK in Augmented Reality abilities. This article aims to identify science teachers’ level of TPACK in Augmented Reality using a questionnaire. A group of teachers (n=100) was trained to determine science teachers' TPACK at AR levels. Selected Science teachers then responded to a survey and analyzed using the Rasch Model. Male teachers (1.77 logits) outperformed female teachers (-0.55 logit) in TPACK abilities. In addition, teachers 36-40 years of age with 6-10 years of teaching experience had higher ability in TPACK in AR. Findings also indicated the Pedagogical Knowledge (PK) scoring is at +1.23logit and TPACK +0.29 logit suggesting both PK and TPACK components were of higher difficulty level compared to other components.The findings suggest that the training on TPACK in AR especially in the areas of PK and TPACK is necessary and should be based on the teacher’s demographic profile, teaching experiences, and other components of the TPACK framework.